Reply on ‘Comments on ‘A novel approach for determination of nucleation rates and interfacial energy of metallic magnesium nanoclusters at high temperature using non-isothermal TGA models’ by the author Ashis Bhattacharjee, which was published in Chemical Engineering Science 280 (2023) 119043.’ - Srivastava P.; Sabbarwal S.; Kumar Verma V.; Kumar M. (My University, 2025)
The following Letter to the Editor presents a scientific reply addressing the comments put forth regarding a paper titled ‘Comments on A novel approach for determination of nucleation rates and interfacial energy of metallic magnesium nanoclusters at high temperature using non-isothermal TGA models’ by the author Ashis Bhattacharjee, which was published in Chemical Engineering Science 280 (2023) 119043.(Bhattacharjee, 2023) © 2024 Elsevier Ltd